1. By the chain rule,
![(\mathrm dz)/(\mathrm dt)=(\partial z)/(\partial x)(\mathrm dx)/(\mathrm dt)+(\partial z)/(\partial y)(\mathrm dy)/(\mathrm dt)](https://img.qammunity.org/2021/formulas/mathematics/college/b2mtq86dgfifknbjyvxiwlakqwy1t26n9m.png)
I'm going to switch up the notation to save space, so for example,
is shorthand for
.
![z_t=z_xx_t+z_yy_t](https://img.qammunity.org/2021/formulas/mathematics/college/xa6sgd66z98eng3n6lynoezksdprz639bg.png)
We have
![x=e^(-t)\implies x_t=-e^(-t)](https://img.qammunity.org/2021/formulas/mathematics/college/n9kywry3uhad3wphvrzpicotixk4vmly5b.png)
![y=e^t\implies y_t=e^t](https://img.qammunity.org/2021/formulas/mathematics/college/k5dew8przwrqth4kdwza46mqe9num0twje.png)
![z=\tan(xy)\implies\begin{cases}z_x=y\sec^2(xy)=e^t\sec^2(1)\\z_y=x\sec^2(xy)=e^(-t)\sec^2(1)\end{cases}](https://img.qammunity.org/2021/formulas/mathematics/college/7kvivq8w9p9ms7529zsgnpzkcbkh0tlryf.png)
![\implies z_t=e^t\sec^2(1)(-e^(-t))+e^(-t)\sec^2(1)e^t=0](https://img.qammunity.org/2021/formulas/mathematics/college/ty1i44zoymbonh2sc3xxg2itvd5yvi6zim.png)
Similarly,
![w_t=w_xx_t+w_yy_t+w_zz_t](https://img.qammunity.org/2021/formulas/mathematics/college/kk84xqgt78fz6s8eiwggzacdc8pcaxhsq2.png)
where
![x=\cosh^2t\implies x_t=2\cosh t\sinh t](https://img.qammunity.org/2021/formulas/mathematics/college/udg9e66w2qavk25rbi816hzeefqt7ubhsd.png)
![y=\sinh^2t\implies y_t=2\cosh t\sinh t](https://img.qammunity.org/2021/formulas/mathematics/college/guu07v4a3nip74uszirfdhe8wwsbuzec9f.png)
![z=t\implies z_t=1](https://img.qammunity.org/2021/formulas/mathematics/college/6egcbk5kx8wygsliwj1e8m68dwl7nhi74h.png)
To capture all the partial derivatives of
, compute its gradient:
![\\abla w=\langle w_x,w_y,w_z\rangle=(\langle1,-1,1\rangle)/(√(1-(x-y+z)^2))}=(\langle1,-1,1\rangle)/(√(-2t-t^2))](https://img.qammunity.org/2021/formulas/mathematics/college/i597yyagiaonqo4gmrvhwr9puex5688ia8.png)
![\implies w_t=\frac1{√(-2t-t^2)}](https://img.qammunity.org/2021/formulas/mathematics/college/9iilrup81nmlljm0sd535tlzv1bu2vvqi0.png)
2. The problem is asking for
and
. But
is already a function of
, so the chain rule isn't needed here. I suspect it's supposed to say "find
and
" instead.
If that's the case, then
![z_s=z_xx_s+z_yy_s](https://img.qammunity.org/2021/formulas/mathematics/college/xqzm3z1lbdqr7ptl8dsbn7nkeueeq93q5e.png)
![z_t=z_xx_t+z_yy_t](https://img.qammunity.org/2021/formulas/mathematics/college/xa6sgd66z98eng3n6lynoezksdprz639bg.png)
as the hint suggests. We have
![z=\sin x\cos y\implies\begin{cases}z_x=\cos x\cos y=\cos(s+t)\cos(s^2t)\\z_y=-\sin x\sin y=-\sin(s+t)\sin(s^2t)\end{cases}](https://img.qammunity.org/2021/formulas/mathematics/college/xw6wppyg0t4mhblf7fbbke6vl408u4xmo5.png)
![x=s+t\implies x_s=x_t=1](https://img.qammunity.org/2021/formulas/mathematics/college/6us96894w5s4r77jxdgnrggdsigfjt7np0.png)
![y=s^2t\implies\begin{cases}y_s=2st\\y_t=s^2\end{cases}](https://img.qammunity.org/2021/formulas/mathematics/college/mx3c45oicpnzg8qi5ps85kldtllox0jixb.png)
Putting everything together, we get
![z_s=\cos(s+t)\cos(s^2t)-2st\sin(s+t)\sin(s^2t)](https://img.qammunity.org/2021/formulas/mathematics/college/9zhfu74a6h7j549bs6nafzosmh0w7futqk.png)
![z_t=\cos(s+t)\cos(s^2t)-s^2\sin(s+t)\sin(s^2t)](https://img.qammunity.org/2021/formulas/mathematics/college/d51k5h25cr9z23qkdp0jti8abluf7qxs12.png)